PENANGANANAN CHILD ABUSE MELALUI PROGRAM SEKOLAH RAMAH ANAK DI SMPN 9 SURABAYA - Ellanda, Putri Nala; Setyowati, Raden Roro Nanik (Universitas Negeri Surabaya (Unesa), 2023)
This study aims to describe the handling of child abuse through the Child Friendly School program at SMPN 9 Surabaya and analyze teacher constraints in handling child abuse through the Child Friendly School program at SMPN 9 Surabaya. This research was analyzed using Bronfenbrenner's ecological theory which discusses 5 levels of environmental systems that affect and are affected by child development. This research uses a descriptive qualitative-based approach. Informants in this study were selected using purposive sampling technique. The data sources used in this research are primary and secondary data sources. The data collection techniques used were passive participant observation, semi-structured in-depth interviews and documentation. Data analysis techniques were carried out by reducing data, presenting data, and drawing conclusions. Data validity techniques using triangulation techniques. The results of this study are the handling of child abuse through the Child Friendly School program at SMPN 9 Surabaya consists of providing a complaint channel, checking the truth, providing treatment (coaching), and communicating with outside parties (handover). The obstacles faced are the constraints of physical punishment, the constraints of parents/guardians who are less cooperative, and the constraints of student conditions. Constraints on the condition of students in the form of lack of control of students over themselves, lack of motivation to go to school due to family problems, lack of openness of students, and the assumption that child abuse is normal.